Uncertainty avoidance and mutual funds - Keswani, A. (2020)
We study how culture influences mutual funds around the world. Uncertainty Avoidance (UA), which is related to ambiguity aversion, is negatively associated with flow-performance sensitivity, deviation from the fund benchmark, fund alpha, and the fraction of active management across the 25 countries in our sample. This is true even when controlling for an exhaustive set of fund- and country-level characteristics. We also find that a fund’s deviation from its benchmark is not only affected by the UA of its domicile country but also by the UA of its fund family’s country of origin. Our results highlight the importance of considering cultural characteristics, and UA in particular, when studying mutual funds across countries.